Children's experiences and needs in situations of domestic violence: A secondary analysis of qualitative data from adult friends and family members of female survivors. (26th November 2019) - Gregory, Alison; Arai, Lisa; MacMillan, Harriet L.; Howarth, Emma; Shaw, Alison
Abstract: Estimates suggest that 15% of children in the United Kingdom have been exposed to at least one form of domestic violence (DV) during their childhood, with more than 3% having witnessed an incident during the past year. This exposure increases the risk of children suffering both short‐term and long‐term impacts, including effects on their behaviour, social development, physical and mental health, educational attainment and quality of life. In addition, children living in environments where there is DV are at higher risk of maltreatment. Adult relatives and friends of the family often observe the experiences of children in situations of DV, and have the potential to shed light in a way that children and survivors may struggle to articulate, or be reluctant to acknowledge or disclose. Such accounts are largely absent from existing research, and yet bring a perspective which can broaden our understanding of the impact that DV has on children. This paper reports a secondary analysis of qualitative data collected during 21 in‐depth interviews with people across the United Kingdom who were a friend or family member of a woman experiencing DV. An inductive thematic analysis was undertaken and the themes generated were as follows: 'the context of DV: a chaotic and unpredictable home life'; 'the roles children assume within households where there is DV including: witness of, victim of and conduit of violence and abuse', ; 'the impacts of DV on children'; and 'children's coping and resilience'. The implications of these findings are discussed using a basic needs model lens.